2018
DOI: 10.3386/w25330
|View full text |Cite
|
Sign up to set email alerts
|

Two Hundred Years of Health and Medical Care: The Importance of Medical Care for Life Expectancy Gains

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w25330.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…It is noteworthy that these estimates are of similar magnitude to an estimate recently reported by Catillon, Cutler and Getzen (2018). Catillon, Cutler and Getzen (2018) use data for the period 1905-1936 on the same 13 cities considered by CM-2005. These authors also use CM's specification, but omit the city-specific linear trends. 9 They find that filtration is associated with a 4.1 percent (e -.042 -1 = .041) reduction in the total mortality rate.…”
Section: Total Mortalitysupporting
confidence: 85%
See 3 more Smart Citations
“…It is noteworthy that these estimates are of similar magnitude to an estimate recently reported by Catillon, Cutler and Getzen (2018). Catillon, Cutler and Getzen (2018) use data for the period 1905-1936 on the same 13 cities considered by CM-2005. These authors also use CM's specification, but omit the city-specific linear trends. 9 They find that filtration is associated with a 4.1 percent (e -.042 -1 = .041) reduction in the total mortality rate.…”
Section: Total Mortalitysupporting
confidence: 85%
“…In column (3), we omit the city-specific linear trends, which reduces the estimated filtration effect from -13.4 log points to -5.8 log points. This latter estimate is similar to, and statistically indistinguishable from, the estimate reported by Catillon, Cutler and Getzen (2018).…”
Section: Total Mortalitysupporting
confidence: 84%
See 2 more Smart Citations
“…The broad timing of the 1930s decline across all regions in our data is consistent with that found in previous studies. Catillon et al (2018), for instance, documented a trend break in 1936 using national data on influenza and pneumonia mortality. Jayachandran et al (2010) found that sulfa drugs reduced maternal mortality by 24 % to 36 %, pneumonia mortality by 17 % to 32 %, and scarlet fever mortality by 52 % to 65 % from 1937 to 1943.…”
Section: Infectious Mortality Declined Later In Southern Cities Than mentioning
confidence: 99%